Dissecting the Dual Role of the Glial Scar and Scar-Forming Astrocytes in Spinal Cord Injury - Yang, Tuo; Dai, YuJuan; Chen, Gang; Cui, ShuSen (Frontiers in Cellular Neuroscience, 2020)
Recovery from spinal cord injury (SCI) remains an unsolved problem. As a major component of SCI lesion, the glial scar which is primarily composed by scar-forming astrocytes plays important roles in spinal cord regeneration. By reviewing recent studies on the glial scar and scar-forming astrocytes, we briefly discuss glial scar formation and the components of the glial scar. Then, we analyze the dual role of the glial scar in a dynamic perspective, especially focus on the scar-forming astrocytes, to explain the seemingly contradictory findings supporting the beneficial and inhibitory effects of them. Finally, we provide several pieces of advice and remarks on novel therapeutic strategies targeting the glial scar and scar-forming astrocytes.